Influence of Bacterial Fertilizers on the Structure of the Rhizospheric Fungal Community of Cereals South of Western Siberia - Natalia Nikolaevna Shuliko; Olga Valentinovna Selitskaya; Elena Vasilyevna Tukmacheva; Alina Andreevna Kiselyova; Irina Anatolyevna Korchagina; Ekaterina Vladimirovna Kubasova; Artem Yuryevich Timokhin (Agronomy)
The general lack of knowledge on the conditions of Western Siberia (Omsk region) and the taxonomic diversity of zonal soils determines the relevance of these studies. The research was carried out in order to study the effect of complex biologics on the taxonomic diversity of the fungal component of the microbiome of the rhizosphere of cereals and the phytosanitary condition of crops in the southern forest-steppe (meadow-chernozem soil) and subtaiga (gray forest soil) zones of the Omsk Irtysh region (Western Siberia). This work was carried out in 2022–2023, using laboratory studies in combination with field experiments and metagenomic and statistical analyses. The objects of research were varieties of cereals and grain forage crops of Omsk selection: soil microorganisms. The scheme of the experiment involved the study of the following options: varieties of cereals (factor A): spring soft wheat—Omsk 42, Omsk 44, Tarskaya 12; durum wheat—Omsk coral; barley—Omsk 101; oats—Siberian hercules; bacterial preparation for seed inoculation (factor B) without the drug—Mizorin and Flavobacterin. The sampling of the plant rhizosphere for metagenomic analysis was carried out during the earing phase (July). For the first time, the taxonomic composition of the fungal community was determined based on the analysis of amplicon libraries of fragments of ribosomal operons of ITS2 fungi during colonization of crop roots by nitrogen-fixing bacteria in various soil and climatic zones of the Omsk region. The fungal component of the microbiome was analyzed in two zones of the Omsk region (southern forest-steppe and subtaiga). The five dominant phyla of soil fungi were located in the following decreasing series: Ascomycota (about 70%) > Mortierellomycota (about 7%) > Basidiomycota (about 5%) > Mucoromycota (3%) > Chytridiomycota (1%). The five main genera of fungi inhabiting the rhizosphere of cereals are located in a decreasing row: Giberella (6.9%) > Mortierella (6.6%) > Chaetomium (4.8%) > Cladosporium (3.8%) > Rhizopus (3.3%). The predominantly positive effect of biologics of associative nitrogen fixation on the fungal community of the soil (rhizosphere) of experimental sites located in different soil and climatic zones has been established. During seed bacterization, the growth of saprotrophic fungal genera was noted in relation to the control variants Pseudogymnoascus, Chloridium, Clonostachys, Trihoderma, etc., and the fungicidal properties of bacterial strains introduced into the soil were actively manifested relative to phytopathogenic fungi of the genera Alternaria, Blumeria, Fusarium, etc. According to the results of determining the number of infectious structures of Rhizoctonia solani, it was found that the population of the soil with viable cells of this pathogen was 1–3 pcs/g (below the threshold of harmfulness, PV 20 pcs/g of soil), which indicates a favorable phytosanitary situation with respect to the pathogen. The fungicidal effect of the applied bacterial fertilizers on Rhizoctonia solani could not be detected. The number of Bipolaris sorokiniana varied depending on the drug used. In the conditions of the southern forest-steppe zone of the Omsk region (meadow-chernozem soil), the greatest fungicidal effect was noted in Flavobacterin application variants on wheat of the Omsk 42 variety, durum wheat of the Omsk coral variety, and barley; the decrease in conidia relative to the control was 73, 35, and 29%, respectively. In the subtaiga zone of the Omsk Irtysh region (gray forest soil), as in the southern forest-steppe zone, pre-sowing bacterization of seeds with Flavobacterin led to a decrease in Bipolaris sorokiniana in the rhizosphere of wheat of the Omsk 42 variety by 18%, and oats by 27%, to control. The use of the drug Mizorin in some variants of the experiment led to an insignificant decrease in the harmful fungus or had no effect at all.